(R)-α-Aminoadipic Acid: A Versatile Precursor for the Synthesis of D-Amino Acids. (10th October 2013) - Sadiq, Amina; Sewald, Norbert
Abstract : The ready accessibility of ( R )- α -aminoadipic acid by enzymatic cleavage of cephalosporin C (CephC) in the production of 7-aminocephalosporanic acid (7-ACA) on a large scale makes it a favorable chiral pool building block for the synthesis of unusual amino acids. A route for the synthesis of C-5-alkenyl and C-6-alkylidene derivatives of ( R )-pipecolic acid is described which utilizes ( R )- α -aminoadipic acid as the enantiomerically pure starting material. Moreover, the synthesis of azido and triazolyl derivatives of ( R )- α -aminoadipic acid is reported.